Economy-wide effects of a sustainable pathway in the pig sector: A case study in Aragon (Spain). (1st June 2019) - Valiño, Luis; Sarasa, Cristina; Duarte, Rosa
Abstract: Computable General Equilibrium models are widely used in the literature to analyse the global effects of certain events with economic repercussions. The intensity of these events is usually justified, although somewhat vaguely. Based on the implementation of new technologies to certain production processes, we analyse the economic impacts of a replacement in the energy supply, from classical to renewable sources. In particular, this work focuses on the pig sector, due to its relatively high off-grid energy use, taking Aragon (Northern Spain) as a case study because of the significance of the sector in this region. A partial equilibrium approach to evaluate this replacement is first addressed. This partial analysis provides the intensity level of the impact of the change. On the basis of these data, the impact of the energy replacement is simulated using a Computable General Equilibrium model developed for the regional economy of Aragon. Findings show a slight increase in (pig) production and exports, and suggest the convenience of combining partial equilibrium analysis, which involves a mix of engineering and economic issues, to estimate the endogenous increase in efficiency, with general equilibrium models. Highlights: Economic impacts of replacing classical energy with renewable sources are addressed. Partial equilibrium analysis is combined with a general equilibrium model. Pig sector is important and presents a high off-grid energy use in Aragon (Spain). We simulate an endogenous technological improvement in the use of energy.